Enhancing Reading Comprehension Skills of Eleventh Grade Students in SMAN 3 Malang through a Gamified Platform - Syahruhdin, Moch Ekky; Kurniasih, Kurniasih; Ariani, Endah (International Journal of Education, Language, and Religion, 2025)
This Classroom Action Research explores how the incorporation of a gamified learning platform influenced students’ ability to understand written Eleventh Grade Students in SMAN 3 Malang. Framed by principles of intrinsic motivation and ongoing assessment, the initial cycle combined traditional evaluative tasks, structured observations of classroom interactions, and a survey capturing learners’ attitudes toward the intervention. Findings revealed a notable improvement in overall reading performance, with learners demonstrating greater accuracy on platform-based quizzes. Classroom dynamics shifted positively: students were more consistently engaged in learning activities and maintained a quieter, more focused environment. Survey responses indicated that participants experienced a stronger sense of choice in their learning, felt more capable when tackling tasks, and enjoyed closer connections with peers and their instructor. Subsequent cycles will seek to enhance collaborative structures and tailor quiz challenges to better suit diverse proficiency levels.